Avoidance of seismic survey activities by penguins. Issue 1 (December 2017) - Pichegru, Lorien; Nyengera, Reason; McInnes, Alistair; Pistorius, Pierre
Abstract Seismic surveys in search for oil or gas under the seabed, produce the most intense man-made ocean noise with known impacts on invertebrates, fish and marine mammals. No evidence to date exists, however, about potential impacts on seabirds. Penguins may be expected to be particularly affected by loud underwater sounds, due to their largely aquatic existence. This study investigated the behavioural response of breeding endangered African PenguinsSpheniscus demersus to seismic surveys within 100 km of their colony in South Africa, using a multi-year GPS tracking dataset. Penguins showed a strong avoidance of their preferred foraging areas during seismic activities, foraging significantly further from the survey vessel when in operation, while increasing their overall foraging effort. The birds reverted to normal behaviour when the operation ceased, although longer-term repercussions on hearing capacities cannot be precluded. The rapid industrialization of the oceans has increased levels of underwater anthropogenic noises globally, a growing concern for a wide range of taxa, now also including seabirds. African penguin numbers have decreased by 70% in the last 10 years, a strong motivation for precautionary management decisions, including the exclusion of seismic exploratory activities within at least 100 km of their breeding colonies.